A matter of climbing: The first suitability index for artificial water sites to assess architectural barriers for amphibians – A practical tool for ecologists, managers, and conservationists. - Antonio Romano (Global Ecology and Conservation)
Traditional irrigation tanks, drinking troughs, and agricultural wells constitute a vital part of the rural heritage in many countries. These types of artificial water sites (AWSs) play pivotal roles in amphibian breeding and conservation and in connectivity among natural water habitats, particularly in Mediterranean environments. In the framework of the global decline of amphibians and wetland ecosystems, this study explores the suitability of AWSs for amphibians, specifically focusing on their structural design, as certain components may serve as architectural barriers. This study introduces and validates the novel Artificial water sites Suitability Index (ASI), a multi-criteria tool assessing the entry into and exit from AWSs, on a database of 440 sites. The ASI is applicable separately both in evaluating entry into aquatic sites (ASIen) and in evaluating exit (ASIex). Developing the ASI involves considering a range of ecological indicators that reflect the functionality of these artificial aquatic ecosystems. Six architectural factors related to walls, edges and bottom of the AWS were taken into consideration. Field validation was obtained for the ASIen. The ASIen demonstrates high predictive performance, offering a nuanced evaluation of the suitability of each AWS, and it was significantly correlated with the species number hosted in the AWSs. Practical solutions for mitigating architectural barriers for amphibians are proposed, with emphasis on the importance of both entry and exit features. The ASI proves its role as an ecological indicator across three tiers: evaluating current artificial water sites suitability, implementing specific interventions, and establishing guidelines for the construction of new AWSs. This versatility makes it a valuable asset in devising conservation strategies for amphibian habitats, specifically in protected areas and land management, aligning artificial water sites construction with the requirements of amphibians for successful biodiversity conservation.